In situ Intranasal Delivery Systems: Application Prospects and Main Pharmaceutical Aspects of Development (Review) - E. O. Bakhrushina; N. B. Demina; M. M. Shumkova; P. S. Rodyuk; D. S. Shulikina; I. I. Krasnyuk (Разработка и регистрация лекарственных средств, 2021)
Introduction. Intranasal delivery of in situ gel-forming systems is a complex but promising direction. Due to the high cost of developing a new chemical object or genetically engineered modification of biological molecules, pharmaceutical companies are focusing on developing technologies for new delivery systems for existing active pharmaceutical ingredients to improve their effectiveness and bioavailability. In situ systems for intranasal delivery, due to increased viscosity and mucoadhesion to the nasal mucosa, allow overcoming mucociliary clearance and ensuring complete absorption and prolonged release of drugs.Text. The article discusses the main advantages of intranasal in situ delivery systems shown in preclinical studies, as well as approaches to the technology of obtaining and standardization of these systems. The results of scientific research in this field over the past 15 years are summarized, the most promising polymers for creating thermoreversible and pH-sensitive compositions are identified, and modern methods for evaluating the sol-gel transition in situ are analyzed.Conclusion. The use of in situ systems for intranasal administration allows providing a high targeting of the delivery of synthetic and biological molecules to the brain. Currently, numerous pharmacokinetic and pharmacodynamic preclinical studies confirm the effectiveness of such systems, as well as their safety. Thermoreversible commercially available and directionally synthesized polymers (poloxamer 407, PLGA, NIPAAm, etc.), as well as chitosan, remain the most popular for the design of in situ delivery systems. In vitro and ex vivo methods with mucosa and artificial nasal fluid are widely used to assess the parameters of in situ gelation, but to increase the reproducibility of the methods and improve the correlation in vitro/in vivo, it is recommended to conduct modeling of the nasal cavity. Developing the technology and methods of screening of intranasal reversible systems will help to get closer to clinical trials and the entry of these delivery systems into the global pharmaceutical market.